2001
DOI: 10.1017/s0952836901001613
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the loggerhead turtle Caretta caretta in the western Mediterranean

Abstract: We studied the feeding ecology of juvenile loggerhead turtles Caretta caretta in the western Mediterranean based on the contents of the digestive tract of 54 turtles (range of CCL: 34±69 cm) seized in Barcelona (Spain) in 1991. Turtles had been captured in ®shing trawls, but speci®c information about dates and localities is not available. Despite this limitation, we obtained interesting evidences about the foraging strategies of loggerheads, with potentially important conservation implications. We report 33 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 14 publications
3
95
0
1
Order By: Relevance
“…However, pelagic red crabs occurred at lower frequencies and fish occurred at higher frequencies compared with previous studies with considerably smaller sample sizes (Ramirez-Cruz et al 1991. Loggerheads are opportunistic, generalist foragers and are known to consume fish as fisheries discards and directly from fishing gear (Shoop & Ruckdeschel 1982, Tomas et al 2001. The fish species retrieved from stomachs in this study were demersal predators of no commercial value that are frequently caught and discarded by local gillnetters (J. Lucero-Romero pers.…”
Section: Discussionmentioning
confidence: 99%
“…However, pelagic red crabs occurred at lower frequencies and fish occurred at higher frequencies compared with previous studies with considerably smaller sample sizes (Ramirez-Cruz et al 1991. Loggerheads are opportunistic, generalist foragers and are known to consume fish as fisheries discards and directly from fishing gear (Shoop & Ruckdeschel 1982, Tomas et al 2001. The fish species retrieved from stomachs in this study were demersal predators of no commercial value that are frequently caught and discarded by local gillnetters (J. Lucero-Romero pers.…”
Section: Discussionmentioning
confidence: 99%
“…longer-duration deployments, improved image quality, and a better camera angle) are required to make stronger inferences. Second, large body size might be expected to lead to an increasingly general diet, as larger turtles are able to feed on larger prey (Tomas et al 2001) but may continue to feed on small items, which was observed in the same turtle's AVED deployment. Increased prey diversity in larger turtles has been noted in loggerhead stomach contents (Tomas et al 2001, but see Limpus et al 2001, although this diversity could also reflect bias due to larger stomach (i.e.…”
Section: Site Specialists Diet Generalists?mentioning
confidence: 98%
“…Furthermore, intrapopulation variation in foraging behavior and diet is an important, unresolved issue (Vander Zanden et al 2010). While it is known, generally, that loggerheads consume diverse invertebrate taxa at the population level (reviews in Dodd 1988, Bjorndal 1997; see also Plotkin et al 1993, Casale et al 2008, Lazar et al 2011, relatively less is known about potential foraging variation within populations related to factors such as size, sex, regional influences, or individual specializations (but see , Tomas et al 2001, Hatase et al 2002, Hawkes et al 2006). Such information is necessary to improve our understanding of loggerheads' functional roles and evaluate the efficacy of management strategies (Hamann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is not a simple task, since loggerhead turtles in the neritic stage are known to feed throughthe whole water column (Bolten 2003), so that finding pelagic and benthic prey in the same sample (e.g. Tomas et al 2001) is not proof of a transitional stage.Small loggerhead turtles (minimum size: 29.5 and 22 cm respectively; Casale et al 2004aCasale et al , 2007a, have been caught by bottom trawlers in 2 of the few wide continental shelves of the Mediterranean basin, the north Adriatic and the central Mediterranean Sea, and an early recruitment to the north Adriatic neritic area was hypothesized (Casale et al 2005a, Lazar et al in press). On the other hand, loggerhead turtles caught by pelagic longliners have been assumed to be in the oceanic stage, in contrast to the assumption that those caught by bottom trawlers are in the neritic stage, and this has important implications for the interpretation of data and patterns in the Mediterranean Sea (e.g.…”
mentioning
confidence: 99%